2021
DOI: 10.1590/s1413-415220190038
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerabilidade domiciliar em situação de intermitência no abastecimento de água

Abstract: RESUMO Os sistemas de abastecimento em regime de intermitência fornecem água aos usuários por um período limitado de tempo, produzindo efeitos adversos à rede de abastecimento de água e aos usuários do sistema, em especial os usuários domésticos, cuja demanda é pouco flexível e a capacidade de adaptação limitada. Neste trabalho é proposto um conjunto simplificado de indicadores que permite identificar diferentes níveis de vulnerabilidade ao desabastecimento de água aos quais uma população urbana está sujeita e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…(20) A study carried out in Campina Grande, the second most populous municipality in the state of Paraíba, identified that the city has flaws in the water distribution system, as confirmed in this study; our data showed that this municipality had one of the least adequate water supply systems. (21) Poor water supply conditions are also related to the socioeconomic conditions of the population, since inadequate housing standards and low incomes have been associated to poor sanitation and water distribution conditions, in addition to gaps in the implementation of adaptation measures in households. (21) Regarding socioeconomic aspects, the municipalities of Campina Grande, João Pessoa, and Cabedelo had the highest average household incomes, indicating that these cities have more resources for the diagnosis and notification of microcephaly cases.…”
Section: ❚ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(20) A study carried out in Campina Grande, the second most populous municipality in the state of Paraíba, identified that the city has flaws in the water distribution system, as confirmed in this study; our data showed that this municipality had one of the least adequate water supply systems. (21) Poor water supply conditions are also related to the socioeconomic conditions of the population, since inadequate housing standards and low incomes have been associated to poor sanitation and water distribution conditions, in addition to gaps in the implementation of adaptation measures in households. (21) Regarding socioeconomic aspects, the municipalities of Campina Grande, João Pessoa, and Cabedelo had the highest average household incomes, indicating that these cities have more resources for the diagnosis and notification of microcephaly cases.…”
Section: ❚ Discussionmentioning
confidence: 99%
“…(21) Poor water supply conditions are also related to the socioeconomic conditions of the population, since inadequate housing standards and low incomes have been associated to poor sanitation and water distribution conditions, in addition to gaps in the implementation of adaptation measures in households. (21) Regarding socioeconomic aspects, the municipalities of Campina Grande, João Pessoa, and Cabedelo had the highest average household incomes, indicating that these cities have more resources for the diagnosis and notification of microcephaly cases. A study conducted in the state of Rio Grande do Norte found a relationship between average household income and the average incidence rate of the Zika virus in 2015 and 2016, which was attributed to better access to health services found in capital cities and metropolitan regions.…”
Section: ❚ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, discontinuity of water supply produces other adverse effects, such as deterioration of water networks designed for continuous supply, leading to leaks and modification of the water quality standard. Consequently, users adapt to meet adversities, highlighting the inequality and vulnerability to shortages to which a city or region is exposed [45]. An intervention study that considered households before and after the installation of piped water showed that the replacement of surface water by piped water utilization occurs significantly only when more water is used (more than 1,000 liters of piped water per person per year).…”
Section: Discussionmentioning
confidence: 99%
“…The WS irregularity data is considered without specifying how many hours or days events occur. Besides that, different areas of the municipalities show specific degrees of irregularity according to their different physical and socio-economic characteristics (Diniz, 2019). Irregularity are factors that can accentuate inequalities within municipalities, and diseases are often identified with location within cities.…”
Section: Methodsmentioning
confidence: 99%